1959
DOI: 10.1083/jcb.6.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Cellular Inclusions in Measles Virus Infections

Abstract: Cells which are infected with measles virus have been known for some time to contain inclusion material that is distinguishable from normal cellular components by application of traditional staining methods and observation in the light microscope. The fine structure of the inclusion material contained in HeLa cells infected with Edmonston strain of measles virus has been examined in the electron microscope. Two steps have been found necessary in this study: (1) the recognition by phase-contrast microscopy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

1964
1964
1980
1980

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 9 publications
1
7
1
1
Order By: Relevance
“…Electron micrographs of tissues infected with measles virus have shown many fibrous filaments VI~w hich occur in both the cytoplasmic and intranuclear inclusion bodies (2,8,10,(13)(14)(15)(16). In our study, inclusion bodies with filamentous fibers were observed in the cytoplasm of HeLa cells 18 to 20 hr after infection with measles virus.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Electron micrographs of tissues infected with measles virus have shown many fibrous filaments VI~w hich occur in both the cytoplasmic and intranuclear inclusion bodies (2,8,10,(13)(14)(15)(16). In our study, inclusion bodies with filamentous fibers were observed in the cytoplasm of HeLa cells 18 to 20 hr after infection with measles virus.…”
Section: Discussionsupporting
confidence: 57%
“…In 1954, Enders and Peebles originally described the appearance of cytoplasmic and intranuclear inclusion bodies in cells infected in vitro with measles virus (6). Kaliman et al (8) and Tawara et al (16) described the filamentous nature of the intranuclear and cytoplasmic inclusion bodies in the measles-infected HeLa cells. These filamentous fibers appeared to be tubular structures of about 15 to 20 nm in outer diameter; they seemed to occur randomly at the early stage of cellular infection and to aggregate to crystalline arrangement in the later stage (14, 15).…”
mentioning
confidence: 99%
“…As shown in Figs. la and 1b, a mass of tubular structures with a diameter of 120 to 1 30 A is seen in a location of the cyto plasm which exactly coincided with the location of the inclusion body optically de tectable by Kallman's method [5]. These structures run parallel with one another and a cross section reveals a regular ar rangement in lattice form.…”
Section: Biological Characteristics Of Hela Cellsmentioning
confidence: 54%
“…The interpretation of the actual nature of these structures is still a matter of speculation, but a viral organism is strongly favoured. The size of the filamentous formations, their fine structure, and their clustering in nuclei, all closely resemble the nuclear changes seen in cells infected in vitro by measles virus (Kallman et al 1959) and in neural cells infected by the virus of subacute sclerosing panencephalitis (SSPE) both in uitro (Raine et al 1974b) (Raine et al 1974a). Similar filaments were reported in muscular cells in a case of chronic polymyositis, so that a myxovirus aetiology was suggested for this disease (Chou Shi-Ming 1967,1968.…”
Section: Discussionmentioning
confidence: 95%